Innovative cooperation among small medium-sized enterprises: from the perspective of multi-department symbiosis. (28th July 2022) - Luo, Yuyan; Wu, Bingqian; Liu, Tingting; Li, Maoyan; Su, Zerui
Synergetic innovation has become an important way of technological innovation for small medium-sized enterprises (SMEs). To this end, this study constructs several research models with synergetic innovation mechanism and synergetic innovation network as moderating variables according to different forms of synergetic innovation networks, so as to verify the stability of the structural equation model to a certain extent. At the same time, for synergetic innovation mechanism and different forms of synergetic innovation network composed of two regulating variables in synergetic innovation model and synergies between possible adjustment effects are discussed in this paper. The results help small and medium-sized enterprises in synergetic innovation, cooperative innovation mechanism and partner selection decisions, which in turn eventually make the enterprise innovation ability get promoted, and achieve long-term high quality development.